NEOPTERIN AND INTERFERON-GAMMA AS IMMUNE RESPONSE MARKERS IN BETATHALASSEMIA MAJOR PATIENTS - Obeid, Shahad F; Al-a'araji, Sanad B; Matti, Bassam F; Fawzi, Hayder Adnan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The assessment of neopterin and interferon-gamma (IFN-Î³) levels as a part of immune system response about serum iron status in Î²-thalassemia (TM) major patients. Methods: Spectrophotometry applied for the estimation of iron status including serum iron level, total iron-binding capacity, and unsaturated iron-binding capacity. Enzyme-linked immunosorbent assay (ELISA) applied for the estimation of the serum cytokines included neopterin and IFN-Î³ also serum ferritin estimation by ELISA from 130 Î²-TM major patients where they divided according to serum ferritin level (< and â‰¥2500 ng/mL). Results: The neopterin and IFN-Î³ concentration showed significantly increased with direct correlation among TM patient group when compared to the normal healthy control group. However, there was no significant difference between different levels of serum ferritin. Conclusion: The increased serum level of neopterin and IFN-Î³ found in patients with Î²-TM may be due to the direct effect of iron on cellular immune cells beside of immune system response to the effect of iron toxicity on different body organs. There was a direct moderate relationship between neopterin and IFN-Î³.